PENGARUH MOTIVASI, PELATIHAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA RUMAH SAKIT UMUM DAERAH MANDAU KABUPATEN BENGKALIS - Gusmalinda Oktavia; Nuryanti Nuryanti; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine whether: 1) there is an effect of motivation on employee performance at the Mandau general hospital, 2) there is an effect of training on employee performance at the Mandau general hospital, 3) there is an influence of the work environment on employee performance at a general hospital. Mandau area. This type of research is quantitative descriptive with primary data derived from questionnaire respondents, which amounted to 148 respondents. The location of this research was carried out at the Mandau general hospital. The sampling technique used was purposive sampling. To determine the size of the sample taken from the population, the researcher uses the formula proposed by Slovin in Mustafa (2010) with a 95% confidence level with a value of e = 5%. The results of this study indicate that: 1) there is a positive and significant effect of motivation on employee performance at the Mandau regional general hospital, 2) there is a positive and significant influence on training on employee performance at the Mandau regional general hospital, 3) there is a positive and significant influence on the environment. work on employee performance at the Mandau regional general hospital.Keywords : Work Motivation, Training Work Environment and Employee Performance